The 126- and 183-kilodalton proteins of tobacco mosaic virus, and not their common nucleotide sequence, control mosaic symptom formation in tobacco. - Bao, Y (1996)
Nucleotide substitutions at two positions within the open reading frame encoding the 126-kDa protein in the attenuated masked (M) strain of tobacco mosaic tobamovirus (TMV) to those found in the virulent U1-TMV genome led to the induction of near U1-TMV-like symptoms on leaves of Nicotiana tabacum L. cv. Xanthi nn by progeny virus (M. H. Shintaku, S. A. Carter, Y. Bao, and R. S. Nelson, Virology 221:218-225, 1996). In this study, further site-directed mutations were made at these positions within the M strain cDNA to determine whether the protein or nucleotide sequence directly controlled the symptom phenotype. The protein and not the nucleotide sequence directly controlled the symptom phenotype when amino acid 360 within the 126-kDa protein sequence was altered and likely controlled the symptom phenotype when amino acid 601 was altered. The effects of the substitutions at amino acid position 360 on viral protein accumulation were studied by pulse-labeling proteins in infected protoplasts. Accumulation of the 126- and 183-kDa proteins was less for an attenuated mutant than for two virulent mutants, but the viral movement protein and coat protein accumulated to levels reported to be sufficient for normal systemic symptom development. The size of necrotic local lesions on N. tabacum L. cv. Xanthi NN was negatively correlated with symptom development and accumulation of the 126-kDa protein for these mutants. With reference to this last finding, an explanation of the cause of the differing symptoms induced by these viruses is presented.